Central ocellus of extinct cockroaches (Blattida: Caloblattinidae) - Vršanský, Peter (Zootaxa, 2008)
Third, central ocellus, lost in living cockroaches, is discovered in the diverse Upper Jurassic representatives of the family Caloblattinidae. Three new genera possessing central ocellus are described: Decomposita triocella gen. et sp. nov.; Srdiecko tri gen. et sp. nov.; Paleovia praecarnia gen. et sp. nov. Presence of central ocellus, although a plesiomorphy, in the Caloblattinidae falsifies the last argument against their ancestral position in respect to mantises (via the Liberiblattinidae).